Implementation of M-Flex Based Moodle in Pancasila Course: An Initial Evaluation on Student’s View - Juliana Tirza (Edukasi: Jurnal Pendidikan, 2021)
Abstract M-Flex is the approach used by utilizing various interesting and quality online learning maneuvers. Moodle-based M-Flex learning specifically in Pancasila learning is the focus of this research. The research aimed to see students' initial responses to Moodle-based M-Flex and monitor any benefits and security felt by users. The approach used is qualitative, with interviews as research instruments. The research respondents were 9 students. Analysis procedures used descriptive qualitative methods. In conclusion, the application of M-Flex based on Moodle still faces several challenges related to students' internet connections, the lack of training in using Moodle for students in Pancasila classes, and the assessment design which is still less varied. M-Flex based on Moodle, on the other hand, shows an advantage because it is supported by Moodle features that continue to develop. AbstrakM-Flex adalah pendekatan yang digunakan dengan memanfaatkan berbagai manuver pembelajaran dalam jaringan yang menarik dan berkualitas. Pembelajaran M-Flex berbasis Moodle khusus dalam pembelajaran Pancasila dijadikan fokus dalam penelitian. Tujuan penelitian untuk melihat respons awal mahasiswa terhadap M-Flex berbasis Moodle dan memantau setiap manfaat serta keamanan yang dirasakan oleh penggunanya. Pendekatan yang digunakan adalah kualitatif dengan wawancara sebagai instrumen penelitian. Responden penelitian sebanyak 9 mahasiswa. Prosedur analisis menggunakan metode deskriptif kualitatif. Kesimpulannya penerapan M-Flex berbasis moodle masih menghadapi beberapa tantangan terkait koneksi internet mahasiswa, kurangnya pelatihan penggunaan moodle bagi mahasiswa dalam kelas Pancasila dan rancangan asesmen yang masih kurang variatif. M-Flex berbasis Moodle di sisi lain memperlihatkan keuntungan karena ditunjang fitur moodle yang terus berkembang.